BIOMETRY OF Artemia franciscana FROM THREE DIFFERENT BATCHES - Siti Hudaidah (JOURNAL OF COASTAL DEVELOPMENT, 2009)
Biometry of Artemia franciscana from three different batches were characterized under laboratoryconditions. The results from diameter measurement of cyst from PR, SI and AS batches were 240 μm, 238μm and 245 μm respectively. The diameter of decapsulated cyst from the same batches were 223 μm (PR),221 μm (SI) and 220 μm (AS). The length of Instar I nauplii from PR, SI and AS batches were 476 μm, 497μm and 498 μm. Hatching efficiency after 48 hours of incubation were 2.76 x 105 nauplii/g cyst, 2.80 x 105nauplii/g cyst and 2.90 x 105 nauplii/g cyst from PR, SI and AS batches. The statistical analysis of theresults indicated that there were no significant differences (P=0.1) in diameter of cyst, length of Instar Inauplii and hatching efficiency of cyst. The hatching percentage of cyst from AS batch at 24 hours (89%),and respectively 48 hours (91%), was significantly higher (P=0.1) than those of SI (83% and 88%) and PR(74% and 80%).The hatching percentage of cyst from PR batch was significantly lower (P=0.1) than SI.